Aortic intramural haematoma: pathogenesis, clinical features and imaging evaluation. Issue 1045 (14th September 2012) - Hoey, Edward T D; Wai, Debbie; Ganeshan, Arul; Watkin, Richard W
Abstract : Intramural haematoma (IMH) is a localised haemorrhage within the aortic wall. Imaging plays a central role in diagnosing IMH, differentiating it from aortic dissection (AD) and assessing for complications. Imaging is also important for prognostication and to help guide clinical decision making as a number of imaging characteristics have been correlated with increased mortality rates including location, mural thickness and aortic diameter. Multidetector CT is the leading technique for diagnosis and classification of IMH owing to speed of image acquisition, multiplanar capabilities and excellent spatial resolution. MRI is rarely used to investigate the initial presentation of IMH but is frequently used for serial follow-up studies. The clinical outcome of IMH may be favourable, with spontaneous regression over time, or it may be complicated by pericardial tamponade, aortic regurgitation and development of AD. Early surgical management is the treatment of choice for patients with Stanford type A IMH whereas most patients with Stanford type B IMH have a good short-term outcome with aggressive control of hypertension. This article reviews the pathogenesis, clinical features and complications of IMH as well as the role of advanced imaging techniques in its evaluation.